Contending with Sexual Harassment: A Study of Southern African Female Journalists’ Experiences - Msimanga, Mbongeni Jonny; Tshuma, Lungile Augustine; Matsilele, Trust; Jamil, Sadia (The Journal of communication inquiry, 2023)
This paper seeks to contribute to the growing literature on sexual harassment of female journalists from the Global South more broadly and Southern Africa in particular. We selected three Southern African countries for this investigation: Zimbabwe, South Africa, and Namibia. Much of sub-Saharan Africa still experiences patriarchy that has proven to be resilient with misogynistic residue. Theoretically, the study utilizes the new institutionalism theory that deals with the socio-political environment within which news organizations are embedded and the postcolonial feminist theory. Primarily, this study uses the qualitative method of semi-structured interviews with 15 journalists across the three countries and offers a thematic analysis of the gathered data. Female journalists’ responses in the selected three countries reveal that they are facing sexual harassment in various forms including, both verbally and physically. The sexual harassment that female journalists are subjected to, we argue, is in part a result of inadequate policies and media regulatory bodies that can curb harassment.